Apprenticeships should work for women too!. Issue 6 (11th July 2016) - Simon, Linda; Clarke, Kira
Abstract : Purpose: – The purpose of this paper is to explore some of the issues affecting successful employment outcomes for young women in male-dominated careers, focusing on those generally accessed via a traditional Australian apprenticeship model. Current patterns of participation in trades-based fields of education and training reinforce the highly gender segregated nature of the Australian Labour Force. Women are particularly under-represented in the large industries of construction, mining and utilities, where female employees account for only around 12, 15 and 23 per cent of employees, respectively, an issue of concern both in terms of increased economic participation of women and girls, and gender equality more broadly. The foundations for transition from education and training to employment are established during school. It is during these formative years that young men and women have notions of what is possible for them, and what is not possible, reinforced. Unfortunately, gendered stereotypes and perceptions around certain career options for young women are still reinforced within schools and create barriers to widening young women's participation in a range of careers, particularly in fields traditionally dominated by males. The paper discusses strategies supporting initial apprenticeship opportunities for young women, and supportive structures to help women and girls build careers in these industries. Design/methodology/approach: – This paper draws from a mixed method study, involving a national electronic survey of educators, industry and community groups, and a range of semi-structured interviews. Whilst the major study focused primarily on career exploration in relation to young women taking on careers in science, technology, engineering and mathematics and non-traditional industries, this paper focuses on one aspect of this study, young women taking up an apprenticeship in a male-dominated career. The research around career exploration was undertaken in 2014, and this paper has placed it in the current context of falling apprenticeships and increasing pressures to increase the number of women and girls employed in a wider range of careers. Findings: – The findings of this particular study consider the barriers to young women taking on apprenticeships and identify strategies that hopefully will produce more successful pathways. This paper can be seen as adding to the public discourse to address the Australian Government's stated reform objective in vocational education and training (VET), that trade apprenticeships are appropriately valued and used as career pathways. Originality/value: – This paper can be seen as adding to the public discourse to address the Australian Government's stated VET reform objective, that trade apprenticeships are appropriately valued and used as career pathways.